PROSES PEMBUATAN ALAT MUSIK SAPE DI DESA CAPKALA KABUPATEN BENGKAYANG - Karlina, Ani; Muniir, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The background of this research was the researcher desire to ducomentation process of making sape to keep it sustainable and growing. Sape is a traditional dayak musical instrument in Kalimantan Indonesia and Sarawak Malaysia made from wood, in addtiion, sape music instrument also has a unique music and melodious. The problem research was the tools used and the process of making sape.This research aimed to described the tools used and the process of making sape instruments in the capkala village. The research method was descriptive qualitative with organological approach. Data collected used was observation, interview with speakers was Dominikus Uyub, and documentation technique. Based on the data results of research, the tools used of making sape is sinso, ax, ketam, chisel, hammer, meter, electric drill, saw, sandpaper, carving tool, and knife. The process of making sape includes the formation of the wooden beam, the drying of the wooden beam, the formation sape body, smoothing, the making of resonation hole, carving Keywords: Process, Sape Making, Capkala Village